2008
DOI: 10.1007/s00408-008-9105-7
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability and Disease Characteristics in Patients with COPD

Abstract: Heart rate variability (HRV) is reduced in patients with chronic obstructive pulmonary disease (COPD). However, the relationships among HRV and characteristics of COPD are unknown. The aim of this study was to characterize HRV in patients with COPD and to verify the correlation of HRV measured during rest with disease severity and pulmonary, muscular, and functional impairment. Thirty-one patients with COPD (16 male; 66 +/- 8 years; BMI = 24 +/- 6 kg/m(2); FEV(1) = 46 +/- 16% predicted) without severe cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 45 publications
2
63
1
3
Order By: Relevance
“…This would lead to increased end-inspiratory lung volume, which is somewhat independent of tidal volume 4 . Although Camillo et al 33 showed that COPD severity was not significantly related to HRV indices, the limited number of subjects classified as GOLD stage II in the current sample might be considered a limitation of the present study. In addition, the inclusion of a healthy control group (without COPD) may elucidate whether the results shown for the COPD group were effectively caused by the PLB maneuver or whether they were partially affected by the disease itself.…”
Section: Discussionmentioning
confidence: 47%
“…This would lead to increased end-inspiratory lung volume, which is somewhat independent of tidal volume 4 . Although Camillo et al 33 showed that COPD severity was not significantly related to HRV indices, the limited number of subjects classified as GOLD stage II in the current sample might be considered a limitation of the present study. In addition, the inclusion of a healthy control group (without COPD) may elucidate whether the results shown for the COPD group were effectively caused by the PLB maneuver or whether they were partially affected by the disease itself.…”
Section: Discussionmentioning
confidence: 47%
“…Additionally, the inclusion of patients whose COPD severity varied widely could be considered another limiting factor, although most of our patients (63%) were classified according to GOLD as stage II and III. Some studies have indicated an association between low FEV1 and a high risk of cardiovascular disease 51,52 , although Camillo et al 53 observed no association between the degree of bronchial obstruction and the values of HRV indices.…”
Section: Discussionmentioning
confidence: 99%
“…Other illnesses and comorbidities that manifest with a ramping up of sympathetic tone also present with a decrease in heart rate variability, such as seen in exacerbation of chronic obstructive pulmonary disease [34] or various infectious states [35]. Examination of all parameters captured by the implantable device will give a more complete understanding of the patient's clinical picture.…”
Section: Heart Rate Variabilitymentioning
confidence: 99%